COMPOSITION AND ELECTRONIC PROPERTIES OF FILM CoSiO BY ION IMPLANTATION - S.B. Donaev; B.E. Umirzakov; B.D. Donaev (International Journal of Innovations in Engineering Research and Technology, 2021)
The morphology, composition and electronic properties of the CoSiO film obtained on the CoSi2/Si (111) surface by implantation of O2+ ions in combination with annealing were studied. Parameters of energy zones are determined and information about the density of the state of electrons of the valence zone and conductivity zone is obtained. In particular, it is shown that the band gap width of this film is 2.4 eV. It was ascertained that the CoSiO/Si/CoSi2 heterosystem is very promising for creating efficient solar energy devices.